Rationale for interleukin-6 blockade in systemic lupus erythematosus - Tackey, E (2004)
Interleukin-6 (IL-6) is a pleiotropic cytokine with a wide range of biological activities that plays an important role in immune regulation and inflammation. Among other actions, it induces terminal differentiation of B lymphocytes into antibody-forming cells and the differentiation of T cells into effector cells. IL-6 also has multiple potent proinflammatory effects. An association between IL-6 and lupus was demonstrated in murine models of SLE and blocking IL-6 improved lupus in all models tested. Data from several studies suggest that IL-6 plays a critical role in the B cell hyperactivity and immunopathology of human SLE, and may have a direct role in mediating tissue damage. Based on these data, we propose that blocking the effect of IL-6 in humans may improve lupus by interacting with the auto inflammatory process both systemically and locally.